Suprathermal electron production in laser-irradiated Cu targets characterized by combined methods of x-ray imaging and spectroscopy. (3rd June 2016) - Renner, O; Šmíd, M; Batani, D; Antonelli, L
Abstract: In a series of experiments performed with laser-irradiated planar targets at the PALS laser facility, the generation of suprathermal electrons has been studied at conditions relevant for the development of a shock ignition approach to inertial confinement fusion. A simultaneous application of high-collection-efficiency K-shell imaging with high resolution x-ray spectroscopy offers a novel approach to hot electron diagnosis at non-coated or moderately coated, medium-atomic-number targets, where the contribution of suprathermal-electron-generated, frequency-shifted K α emission from highly ionized atoms cannot be neglected. Based on experimental data provided by these combined techniques and their interpretation via collisional-radiative atomic codes and Monte Carlo modeling of hot electron energy deposition in heated Cu targets, the fraction of the energy converted to hot electrons at laser intensities ≈10 16 W cm −2 was measured to be at the level of 0.1–0.8%. The higher values of conversion efficiency found for frequency tripled radiation support a theoretical conjecture of enhanced laser energy absorption by a resonance mechanism and its transport to a flow of fast electrons.